Macrophomina phaseolina: density and longevity of microsclerotia in soybean root tissues and free on the soil, and competitive saprophytic ability - Reis,Erlei Melo (2014)
In field experiments, the density of Macrophomina phaseolina microsclerotia in root tissues of naturally colonized soybean cultivars was quantified. The density of free sclerotia on the soil was determined for plots of crop rotation (soybean-corn) and soybean monoculture soon after soybean harvest. M. phaseolina natural infection was also determined for the roots of weeds grown in the experimental area. To verify the ability of M. phaseolina to colonize dead substrates, senesced stem segments from the main plant species representing the agricultural system of southern Brazil were exposed on naturally infested soil for 30 and 60 days. To quantify the sclerotia, the methodology of Cloud and Rupe (1991) and Mengistu et al. (2007) was employed. Sclerotium density, assessed based on colony forming units (CFU), ranged from 156 to 1,108/g root tissue. Sclerotium longevity, also assessed according to CFU, was 157 days for the rotation and 163 days for the monoculture system. M. phaseolina did not colonize saprophytically any dead stem segment of Avena strigosa,Avena sativa,Hordeum vulgare,Brassica napus,Gossypium hirsutum,Secale cereale,Helianthus annus,Triticosecalerimpaui, and Triticum aestivum. Mp was isolated from infected root tissues of Amaranthus viridis,Bidens pilosa,Cardiospermum halicacabum,Euphorbia heterophylla,Ipomoea sp., and Richardia brasiliensis. The survival mechanisms of M. phaseolina studied in this paper met the microsclerotium longevity in soybean root tissues, free on the soil, as well as asymptomatic colonization of weeds.